Les particularités phonético-phonologiques du français parlé par les élèves finalistes de quelques écoles secondaires de la ville de Kisangani. - Jacques MUKONKOLE Lukombe (IJRDO- Journal of Educational Research, 2019)
This article examines French as Spoken by pupils of sixth forms in some secondary schools from Kisangani city. This analysis has been carried out on two aspects that is Phonetics and Phonology. As the end of the analysis, is has been revealed that the French language spoken by these pupils is characterized by certain particularities due to linguistic interferences. These ones are consecutive to the difference of phonetic systems of French with local languages in general and which Kiswahili and Lingala, in particular, two languages which are used narrowly with French in this city. Given the inexistence of nasal sounds in the local languages, Congolese pupils assimilate them to the corresponding oral sounds relating to consonants, there in confusion of certain among them.